Communication in cognitive behavioral therapy - Rimondini, Michela (Springer eBooks., 2011)
Research has shown that the therapeutic alliance is a key factor in the success of treatment, and a critical component of establishing this alliance is the communication between therapist and client. The efficacy of treatment depends on the therapist's ability to collect reliable client information and create the foundation for a good relationship that involves the client in the healing process. "Communication in Cognitive Behavioral Therapy" provides an overview of the research and theory underlying the importance of therapeutic communication with a specific focus on cognitive behavior.